Perhitungan dan Pemotongan, Pengisian SPT 1721 Pegawai Terhadap Pelaporan SPT 1721 Pada Dinas ZYX - Syahfalina, Tika; Nugroho, Aditya Nuraini; Suprihatiningsih, Suprihatiningsih; Suratno, Suratno (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
The purpose of this study is to determine the calculation and deduction andfilling of SPT 1721 against reporting SPT 1721 at the ZYX Office. In this study,using a quantitative approach with descriptive analysis methods previouslydata has been obtained from various sources. The total tax payable amountingto Rp 63.328.082 has been paid on March 10, 2020